2020
DOI: 10.1111/gcb.15107
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of unvegetated tidal flats to coastal carbon flux

Abstract: Unvegetated flats occupy a large area in the intertidal zone. However, compared to vegetated areas, the carbon sequestration of unvegetated tidal flats is rarely quantified, even though these areas are highly threatened by human development and climate change. We determined benthic maximum gross primary production (GPP m ), net primary production (NPP) and total respiration (TR) during emersion on seven tidal flats along a latitudinal gradient (from 22.48°N to 40.60°N) in winter and summer from 2012 to 2016 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 68 publications
(108 reference statements)
0
26
0
Order By: Relevance
“…Higher temperatures generally stimulate metabolic processes and photosynthesis rates. Lin et al (2020) further indicated that the effects of temperature on the CO 2 fluxes in tidal flats were non-linear, showing a quadratic relationship with an optimal temperature at which the CO 2 fluxes were highest. In this study, the sediment temperatures in summer ranged from 31.2 • C to 40.6 • C, which far exceeded the optimal temperatures (28.7 • C for GPP m , 26.6 • C for NPP; Lin et al, 2020) for primary production.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Higher temperatures generally stimulate metabolic processes and photosynthesis rates. Lin et al (2020) further indicated that the effects of temperature on the CO 2 fluxes in tidal flats were non-linear, showing a quadratic relationship with an optimal temperature at which the CO 2 fluxes were highest. In this study, the sediment temperatures in summer ranged from 31.2 • C to 40.6 • C, which far exceeded the optimal temperatures (28.7 • C for GPP m , 26.6 • C for NPP; Lin et al, 2020) for primary production.…”
Section: Discussionmentioning
confidence: 95%
“…whenever the sum of NPP and TR was negative, the tidal flat showed heterotrophic conditions; the GPP was then assumed to be zero. Measurements were considered outliers and excluded for further analysis when they fell outside the interquartile range (i.e., between Q1 -1.5 × IQR and Q3 + 1.5 × IQR, where Q1 is the first quartile, Q3 is the third quartile, and IQR is the difference between Q1 and Q3, Lin et al, 2020). At each site in each season, at least 10 random and non-repeating replicates of CO 2 flux measurements were obtained.…”
Section: Carbon Flux Measurementsmentioning
confidence: 99%
See 3 more Smart Citations